Effect of Anchorage Length on the Shear Capacity of High Strength Concrete Deep Beams - Gatea a, Maytham Khalid; A.M.Jawad b, Dr. David (Anbar Journal of Engineering Sciences, 2021)
Ten simply supported deep beams with high strength concrete (C55 MPa) have been casted and subjected to a four-point loading test. Different parameters were examined for their influence on specimen behavior. These parameters were the shear span to overall depth ratio (a/h), the overall depth of deep beams (h), and additional anchorage length beyond the centerline of support (la). The experimental results show that the beam capacity decreases as the shear span to the overall depth ratio increases, and the overall depth and embedment length decrease. The major effect of anchorage length on the shear strength is studied. Different failure modes were observed which do not match strut-and-tie failure modes. The shear compression and anchorage failures were con-trolled in the high compressive concrete deep beams due to bottom steel yielding. Finally, the ex-perimental test results are compared with predictions of the strut-and-tie method according to the ACI 318-14 and a good agreement was found.